2011
DOI: 10.1080/21528586.2011.621231
|View full text |Cite
|
Sign up to set email alerts
|

Coming Out as a Lesbian in Johannesburg, South Africa: Considering Intersecting Identities and Social Spaces

Abstract: The process of coming out is important in trying to understand how a lesbian identity is shaped and re-negotiated within various social spaces in South Africa today. The article argues that it is vital to acknowledge the intersectionality of identities and social spaces in order to understand and conceptualise the coming-out process. The article raises the question how lesbian identities are formed over time and argues that the different stages of identity development are influenced by the individual's other o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Downs 2006: 76) themselves as gay men, with pride (cf. Cass 1984: 116;Smuts 2011). Problematic in such an approach, as Plummer concedes, is the fact that these phases and/or stages condone the homogenisation of homosexual experience.…”
Section: Queer Theory: Towards Internal Denaturalisation and Diversitymentioning
confidence: 94%
See 1 more Smart Citation
“…Downs 2006: 76) themselves as gay men, with pride (cf. Cass 1984: 116;Smuts 2011). Problematic in such an approach, as Plummer concedes, is the fact that these phases and/or stages condone the homogenisation of homosexual experience.…”
Section: Queer Theory: Towards Internal Denaturalisation and Diversitymentioning
confidence: 94%
“…Research has commented on the seeming 'invisibility' of lesbianism in mainstream heterosexual or homosexual culture and academia (Distiller 2005: 45;Dlamini 2006: 128;Fester 2006: 108;Gevisser 1995: 19;Kowen & Davis 2006: 80;Sanger & Clowes 2006: 38), due to the fact that women were not afforded the freedom of choice relating to sexual intercourse with their husbands or even other women, but found their experiences enmeshed in medical and/ or pathological models of inquiry or even initial exclusion from criminalisation because of their 'denied existence' (Sanger & Clowes 2006: 39). Some researchers focused on how lesbianism does not necessarily pose an immediate threat to heteronormativity, whilst others associated physical violence directed towards particularly black lesbians as an outgrowth of both patriarchal and traditional African culture (Kowen & Davis 2006;Muholi 2004: 118;Ochse 2011;Smuts 2011). These studies identified factors such as pathologisation, abandonment, corrective rape and accusations of witchcraft as impediments in accessing lesbian respondents for research objectives.…”
Section: A Case Of Assimilation and Essentialism: Lesbian And Gay Stumentioning
confidence: 96%
“…Jackson and Scott (2010) and Smuts (2011), writing from British and South African perspectives respectively, caution an uncritical view of reflexivity as being only redeeming. One should consider the particular context in which one finds oneself which may necessitate the social (and sexual) actor to engage in a critical selfevaluation and efforts of "impression management" (Goffman 1971).…”
Section: The Reflexive Gay Male On the University Campusmentioning
confidence: 99%
“…This is attributed to the fact that they are required to constantly re-enter, re-emerge and re-create new closets based on the contextual allowances or restrictions with which they are confronted (Smuts 2011). Given contextual constraints, some may not be afforded the opportunity to access the necessary material or human resources which are important to master Cass's (1990) identity synthesis or Seidman's (2002: 75) so-called 'post-closeted gay sensibility'.…”
mentioning
confidence: 99%